Influence of Nanogels on Mechanical, Dynamic Mechanical, and Thermal Properties of Elastomers - Mitra Suman; Chattopadhyay Santanu; Bhowmick Anil (Nanoscale Research Letters, 2009)
Abstract Use of sulfur crosslinked nanogels to improve various properties of virgin elastomers was investigated for the first time. Natural rubber (NR) and styrene butadiene rubber (SBR) nanogels were prepared by prevulcanization of the respective rubber lattices. These nanogels were characterized by dynamic light scattering, atomic force microscopy (AFM), solvent swelling, mechanical, and dynamic mechanical property measurements. Intermixing of gel and matrix at various ratios was carried out. Addition of NR gels greatly improved the green strength of SBR, whereas presence of SBR nanogels induced greater thermal stability in NR. For example, addition of 16 phr of NR gel increased the maximum tensile stress value of neat SBR by more than 48%. Noticeable increase in glass transition temperature of the gel filled systems was also observed. Morphology of these gel filled elastomers was studied by a combination of energy dispersive X-ray mapping, transmission electron microscopy, and AFM techniques. Particulate filler composite reinforcement models were used to understand the reinforcement mechanism of these nanogels.